A bird-eye view of Costa Rica's transport infrastructure - Pisu, Mauro (OECD Economics Department Working Papers, 2016)
Costa Rica's transport infrastructure sector has long suffered from insufficient and ineffective investment and maintenance spending, resulting in a congested and poor-quality transport network. Public spending has been below the OECD average and private sector participation is limited. The road network is extensive but of poor quality, railways are in disrepair and only slowly being reactivated after having been shut down in the 1990s, seaports quality and capacity are deficient. Internal transportation overly relies on private road vehicles as the public transport system, especially railways, is inadequate. As a result, the transport sector is the major source of greenhouse emissions. Major challenges hindering the sector performance are: excessive institutional fragmentation, which reduces transparency and accountability of public sector agencies, poor strategic planning, which results in haphazard infrastructure development and poor intermodal connections, aversion to private sector participation and absence of an infrastructure-project pipeline, which discourage private investment, poor project preparation and slow project execution due to no cost benefit analyses, unclear project selection criteria and insufficient stakeholder engagement. This working paper relates to the 2016 OECD Economic Survey of Costa Rica (www.oecd.org/eco/surveys/economic-survey-costa-rica.htm)